Pengaruh Perhatian Orang Tua dan Disiplin Belajar Terhadap Hasil Belajar IPS Peserta Didik - Aunia Syarif; Maharuddi Pangewa; Patahuddin Patahuddin (Phinisi Integration Review, 2022)
The aims of the study are to discover: (1) the influence of parents’ attention on social studies learning outcomes at SD Inpres Lipukasi in Barru district, (2) the influence of learning discipline on social studies learning outcomes at SD Inpres Lipukasi in Barru district, (3) the influence of parents’ attention and learning discipline on social studies learning outcomes at SD Inpres Lipukasi in Barru district. This study is a quantitative study with a sample of 59 students based on the Krejcie table. Data collection techniques employed questionnaires and documentation. The data analysis technique employed descriptive analysis which included the mean, mode, median, average, and standard deviation values. As well as inferential statistical analysis which included correlation test and regression analysis test. The results show that: (1) there is an influence of parents’ attention on social studies learning outcomes at SD Inpres Lipukasi in Barru district, (2) there is an influence of learning discipline on social studies learning outcomes at SD Inpres Lipukasi in Barru district, and (3) there is an influence of parents’ attention and learning discipline on social studies learning outcomes at SD Inpres Lipukasi in Barru district.